1/12m+2/3m=60m=

Simple and best practice solution for 1/12m+2/3m=60m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/12m+2/3m=60m= equation:



1/12m+2/3m=60m=
We move all terms to the left:
1/12m+2/3m-(60m)=0
Domain of the equation: 12m!=0
m!=0/12
m!=0
m∈R
Domain of the equation: 3m!=0
m!=0/3
m!=0
m∈R
We add all the numbers together, and all the variables
-60m+1/12m+2/3m=0
We calculate fractions
-60m+3m/36m^2+24m/36m^2=0
We multiply all the terms by the denominator
-60m*36m^2+3m+24m=0
We add all the numbers together, and all the variables
27m-60m*36m^2=0
Wy multiply elements
-2160m^3+27m=0
We do not support empression: m^3

See similar equations:

| 1/4x+8=9 | | (17x+7)+(9x+5)=90 | | 3x-1=8-2/3x | | 2/1.5=h/(h+16) | | 77x-70=7(11x-10) | | 10/6m+2=13/6 | | (17x+7)+(9x+5)=180 | | 5x-2=-29 | | 1/12m+2/3m=60 | | 7x+18x-5=5(5x+10) | | -7-6(1+4k)=-22 | | 3x^2+9=18 | | 2/1.5=h/h+16 | | 17=t+3 | | 1/7y-3=-11 | | 27=x/4+5 | | -6b+12=4b-53 | | -5(2b-7)=-3-7(b-5) | | 29x+54=29x+47 | | 17=t3 | | X+7+3x+20=6x-5 | | -3(7b-6)=-29-9b | | 2x+5x+51=180 | | 2.5w-6=7.5w+19 | | 4(x+4)+7x=7+8x | | x-8(8+2x)=20-x | | -28=4r^2 | | 2x^2-1x=21 | | U=4a+4 | | (12x-37)+(9x+5)=180 | | 2(-5x+2)=-6(6+x) | | .75x+5=2 |

Equations solver categories